AYODYAPALA DANCE STUDIO AS AN AGENT OF CULTURAL EVOLUTION: A NEO-EVOLUTIONARY STUDY OF THE PRESERVATION OF SURAKARTA DANCE IN DEPOK CITY - Lusdinda, Febrina Putri (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study aims to analyze the role of the Ayodyapala Dance Studio as an agent of cultural evolutionin the preservation of Surakarta Dance in Depok City through the perspective of Marshall D. Sahlinsand Elman R. Service's Neoevolutionism theory. Depok City, as a buffer urban area for Jakarta,represents a meeting place between tradition and modernity that triggers the process of culturaladaptation and transformation. Using a descriptive qualitative approach and case study method, thisstudy examines the dynamics of traditional dance preservation amidst the socio-cultural developmentof urban society. The results of the study indicate that the Ayodyapala Studio not only functions as aforum for dance education and training, but also as an agent of cultural adaptation that maintainstraditional values through innovation in form, function, and performance media. This phenomenonreflects the concept of specific evolution and evolutionary potential in the Neoevolutionism theory,where cultural preservation takes place through a continuous process of adaptation without losingits original identity. Thus, the Ayodyapala Studio plays an important role in maintaining thecontinuity of the Surakarta Dance tradition while confirming its relevance amidst the current ofmodernization in big cities.